Dilemmas of using the quality of life’s concept for region’s socioeconomic development - Mandys, Jan; Šanda, Martin; Korovchenko, Tetiana (Jihočeská univerzita v Českých Budějovicích, 2016)
Socio-economic development of the region is not derived only from the performance of the local economy and riches of inhabitants. In an effort to achieve equilibrium of the social society, regional management is facing numerous ob-stacles. The main obstacle is finding the method of measuring the degree of satisfying the needs of inhabitants, citi-zens. One of the way for retrospective evaluation of effectivity and effectiveness measures, which are promoting the development of region, is using of concept of quality of life. In the following text are briefly described the basic di-lemmas in definition of quality of life. Then weaknesses of individual procedures are discussed in the examples of specific measurements. The result is a reasoning - how to measure quality of life so as to deliver the expected results for the needs of regional management? The primary issue in our considerations is the minimum number of publicly available data on the subjective quality of life. We consider objective indicators simplistic and often misleading (in relation to an abstract concept to most definitions of quality of life). Because the subject of interest of this concept is the man, we have to look for the intersection of these two approaches. Another important question is to use data ob-tained by regional management in decision making and very definition of the expectations of the regional manage-ment of these data.
Dilemata využití konceptu kvality pro socioekonomický rozvoj regionu
Keywords: Quality of Life, Public Policy, Region, Socio-economic Development; Kvalita života, veřejná politika, region, socio-ekonomický rozvoj